MOOCs Reshaping Undergraduate Health Education: A Systematic Review - Aydemir Arslan, Melike; Ata, Asiye; Kucuk, Sevda (International Review of Research in Open and Distributed Learning, 2026)
Given the growing demand for flexible and accessible health education, massive open online courses (MOOCs) have been recognized as instrumental in expanding undergraduate learning. This systematic review was conducted to investigate the use of MOOCs in undergraduate health education, focusing on publication trends, geographic distribution, and key research variables. A total of 31 peer-reviewed articles were reviewed, and data were sourced from six international databases: Web of Science, Scopus, ERIC, EBSCOHost, ScienceDirect, and PubMed. It was found that MOOCs have been integrated into undergraduate health education since 2014, with a notable increase in publications observed after 2022. The highest number of studies was published in China. Student satisfaction was identified as the most frequently studied variable, and medical education was reported as the dominant field. Quantitative research were predominantly used, with sample sizes between 101 and 300 participants. Questionnaires were commonly employed as a data collection tool, and many studies were based on custom-developed MOOCs for their research. Courses were typically between 4 and 6 weeks duration. Improved clinical skills were frequently reported as outcomes, while the lack of practical experience in MOOC-based learning was identified as a major limitation. More practice-oriented teaching approaches were recommended by most studies. To enhance the effectiveness of MOOCs in health education, more innovative and practical implementation strategies are needed. Future research is encouraged to address these gaps and strengthen the impact of MOOCs on undergraduate health programs. The growing role of MOOCs in health education is highlighted, particularly the need to integrate practical components for greater educational impact.